PENERAPAN TERAPI RENDAM KAKI DENGAN AIR JAHE HANGAT TERHADAP PENURUNAN NYERI PADA PASIEN ARTHRITIS GOUT DI PUSKESMAS MUNGKID KABUPATEN MAGELANG - Endro Haksara; Ainnur Rahmanti (Pusat Riset dan Inovasi Nasional, 2022)
Gouty arthritis is a disease caused by a buildup of uric acid in the joints of the body. Gouty arthritis that is not treated effectively can develop into chronic gout, form tofus, and can lead to severe kidney function impairment, and decreased quality of life. The purpose of the case study was to describe the application of foot soak therapy with warm ginger water to reduce pain in gout arthritis patients at Mungkid Public Health Center, Magelang Regency. This type of research is descriptive using a case study approach. The subjects in this study were two patients diagnosed with gouty arthritis. Data collection was carried out by observing pain scales in patients based on Standard Operating Procedures for measuring patient pain scales before and after warm ginger foot soak therapy. The results of the case study showed that after the implementation of diabetic foot exercises, it was found that there was a decrease in pain levels in subjects I and II. In subject I there was a decrease in the pain scale from a pain scale of 8 (severe) to a mild scale of 3 and in subject II there was a decrease in the pain scale of 7 (moderate) to a scale of 2 (mild). The conclusion of the case study is that the application of foot bath therapy with warm ginger water is effective in reducing pain levels in gouty arthritis patients. Recommendations need to apply foot soak therapy with warm ginger water to reduce pain levels in patients with diabetes arthritis gout.